Microarray analysis of the in vivo response of microglia to Aβ peptides in mice with conditional deletion of the prostaglandin EP2 receptor - Johansson, Jenny U. (Genom Data, 2015)
Amyloid-β (Aβ) peptides accumulate in the brains of patients with Alzheimer's disease (AD), where they generate a persistent inflammatory response from microglia, the innate immune cells of the brain. The immune modulatory cyclooxygenase/prostaglandin E2 (COX/PGE(2)) pathway has been implicated in preclinical AD development, both in human epidemiology studies and in transgenic rodent models of AD [2,3]. PGE(2) signals through four G-protein-coupled receptors, including the EP2 receptor that has been investigated for its role in mediating the inflammatory and phagocytic responses to Aβ [4]. To identify transcriptional differences in microglia lacking the EP2 receptor, we examined mice with EP2 conditionally deleted in Cd11b-expressing immune cells. We injected Aβ peptides or saline vehicle into the brains of adult mice, isolated primary microglia, and analyzed RNA expression by microarray. The resulting datasets were analyzed in two studies [5,6], one describing the basal status of microglia with or without EP2 deletion, and the second study analyzing the microglial response to Aβ. Here we describe in detail the experimental design and data analyses. The raw data from these studies are deposited in GEO, accession GSE57181 (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE57181).